FOOD-BASED AND NON-FOOD-BASED INTERVENTIONS TO IMPROVE DIETARY DIVERSITY: A LITERATURE REVIEW - Riska Mayang Saputri Ginting; Nila Reswari Haryani; Sri Sumarmi (Media Gizi Indonesia, 2022)
Dietary diversity is one of the diet quality. Poor dietary diversity is associated with malnutrition, stunting, poor gut health, pregnancy complications, and cognitive impairment. Overcoming the underlying and basic causes of poor dietary diversity is imperative through policymaking. This current literature review discussed about intervention policies to improve dietary diversity at the individual and population levels. Literature search was carried out in some databases, i.e., Pubmed/Medline, Google Scholar, and Google with key word search such as dietary diversity, improvement, programs, interventions, and policies. The synthesized articles included observational studies, experimental studies, and grey literature on Dietary diversity programs and interventions. Articles on biodiversity and microbial diversity were not included. Dietary diversity can outgrow by knowing the policy on food-based interventions which are closely related to the food system and non-food-based interventions to improve socio-economic aspect and knowledge. Food-based interventions include food production, food prices, agricultural diversification, market development, and food-based dietary guidelines. Meanwhile, non-food-based interventions involve a country's development and economic growth, social behavior change, communication strategy, cash transfer, and mass media campaigns. Interventions to improve dietary diversity must be carried out in multi-sectors, for example, by improving family welfare, knowledge and behavior change, and stable food access.